2022
DOI: 10.3389/fphar.2022.910217
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Taohong Siwu Decoction on Cerebral Ischemia/Reperfusion Injury via Mitophagy-NLRP3 Inflammasome Pathway

Abstract: Objective: Globally, cerebral ischemia has been shown to be the second leading cause of death. Our previous studies have shown that Taohong Siwu Decoction (THSWD) exhibits obvious neuroprotective effects on cerebral ischemia/reperfusion (I/R) injury (CIRI). In this study, we further explored the modulatory effect of THSWD on mitochondrial autophagy in CIRI and the relationship between modulatory effect and NLRP3 inflammatory vesicle activation, so as to further explain the mechanism of neuroprotective effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In this study, GSS was found to decrease the high expression of GFAP and GBP2 after HIE in neonatal rats, indicating depressive effects of activation and A1-type polarisation on astrocytes. CD16 is one of the markers of microglial polarisation into the M1 type after activation [ 49 , 50 ]. GSS also reduced the transcription of both CD11b and CD16 mRNA as well as the protein level of CD11b, showing an inhibitory effect on the activation and polarisation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, GSS was found to decrease the high expression of GFAP and GBP2 after HIE in neonatal rats, indicating depressive effects of activation and A1-type polarisation on astrocytes. CD16 is one of the markers of microglial polarisation into the M1 type after activation [ 49 , 50 ]. GSS also reduced the transcription of both CD11b and CD16 mRNA as well as the protein level of CD11b, showing an inhibitory effect on the activation and polarisation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the dehydrogenase activity (DHA) provides important information on the biological activity in many systems. Thus, the reduction of 2,3,5-triphenyltetrazolium chloride (TTC) to triphenylformazan (TPF) has been commonly used to estimate the DHA in soil, and TTC has been widely used as a hydrogen receptor in the enzymatic activity test [34][35][36][37]. Artificial enzyme mimetics have been intensively studied, due to some considerable shortcomings, such as a relatively low stability, and the poor recovery of natural enzymes [30,38].…”
Section: Of 17mentioning
confidence: 99%
“…Taohong Siwu decoction treatment for seven consecutive days decreased damage to mitochondrial structures following cerebral I/R injury ( Ji et al, 2022 ). Treatment with Huang-Lian-Jie-Du decoction, Danhong injection, and Baoyuan capsule eliminated the inhibitory effect of cerebral I/R on mitochondrial metabolism in MCAO models ( Wang et al, 2014 ; Zeng et al, 2021b ; Du et al, 2021 ).…”
Section: Progress In Ischemic Stroke Prevention and Treatment Using T...mentioning
confidence: 99%
“…YiQiFuMai powder injection inhibited the expression, phosphorylation, and translocation of Drp1 in oxidative stress-induced primary neurons and cerebral ischemia-injured rats, resulting in a significant improvement in cerebral infarction and neurological scores ( Xu et al, 2017 ). Taohong Siwu decoction, Danhong injection, and ANNAO tablets upregulated the expression of autophagy markers (LC3-II/LC3-I and Beclin1) ( Ji et al, 2022 ) and mitochondrial autophagy markers (Parkin ( Orgah et al, 2019 ) and PINK1 ( Zhang et al, 2020 )) after cerebral I/R injury. Mu-Xiang-You-Fang inhibits autophagy after OGD/R-induced PC12 cell injury through the AMPK-mTOR pathway ( Ma et al, 2020 ).…”
Section: Progress In Ischemic Stroke Prevention and Treatment Using T...mentioning
confidence: 99%